2001
DOI: 10.1078/0944-5013-00066
|View full text |Cite
|
Sign up to set email alerts
|

Cell lysis in Escherichia coli cultures stimulates growth and biosynthesis of recombinant proteins in surviving cells

Abstract: Cell growth and production of recombinant proteins in stationary phase cultures of Escherichia coli recover concomitantly with spontaneous lysis of a fraction of the ageing cell population. Further exploration of this event has indicated that sonic cell disruption stimulates both cell growth and synthesis of plasmid-encoded recombinant proteins, even in exponentially growing cultures. These observations indicate an efficient cell utilisation of released intracellular material and also that this capability is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This can easily be explained by the fact that inhibiting the growth of plasmid-free cells makes all resources available to plasmid-bearing bacteria. Moreover, cell lysis of the plasmid-free cells could even stimulate growth of surviving (plasmid-bearing) cells, as previously shown by Corchero and coworkers (28). …”
Section: Discussionmentioning
confidence: 66%
“…This can easily be explained by the fact that inhibiting the growth of plasmid-free cells makes all resources available to plasmid-bearing bacteria. Moreover, cell lysis of the plasmid-free cells could even stimulate growth of surviving (plasmid-bearing) cells, as previously shown by Corchero and coworkers (28). …”
Section: Discussionmentioning
confidence: 66%
“…Long-term survival would be possible in fluid inclusions in salt deposits, and the maintenance energy might stem from scarifying a certain fraction of the enclosed population. For E. coli, it has indeed been shown that lysis of a fraction of a stationary-phase culture can even foster growth of the survivors [20].…”
Section: Survival Over Geological Timesmentioning
confidence: 99%
“…The maintenance energy for long-term survival, including the repair of double-strand breaks, might originate from lysis of some or even the majority of cells of the enclosed population. For Escherichia coli, it has indeed been shown that cell lysis promotes growth of the remaining population (Corchero et al, 2001). Recently, three haloarchaeal species have been freshly isolated from an ancient salt deposit, and their ploidy levels have been quantified.…”
Section: Long-term Survival and Survival In Extreme Environmentsmentioning
confidence: 99%